Potential environmental pollution from copper metallurgy and methods of management - Izydorczyk, Grzegorz; Mikula, Katarzyna; Skrzypczak, Dawid; Moustakas, Konstantinos; Witek-Krowiak, Anna; Chojnacka, Katarzyna (Environmental research, 2021)
This paper presents the latest overview of the environmental impact of wastes from the non-ferrous metallurgical industry. Ashes, slags and dusts – by-products from mining and metal processing – are sources of toxic metals, such as Pb, Cd, Hg, As, Al, as well as particulate matter. Physical, chemical and biological processes transform industrial wastes and cause water, soil and air pollution. Improperly protected heaps are subject to wind erosion and rain water leaching. Heavy metals and particulate matter are transported over long distances, contaminating the soil, living areas, watercourses, while in combination with mist they create smog. Water erosion releases heavy metals, which are leached into groundwater or surface runoff. This paper focuses on the range of pollution emissions from non-ferrous metallurgy wastes, hazards, mechanisms of their formation and fallouts, on the current state of technology and technological risk reduction solutions. The impact of pollution on human health and the biosphere, and methods of waste reduction in this industry sector are also presented. A sustainable and modern mining industry is the first step to cleaner production. [Display omitted] •Smelter dusts are a source of toxic metals that are transmitted long distances by air.•Pollutants are leached to surface water and accumulate in bottom sediments.•Accumulation of toxic elements in the soil is a threat to food production.•Metallurgical dusts have major impacts on human health - different routes of exposure.•Pollutants emitted by the copper smelter (dust and gases) pose a threat to biota.